Effects of institutional factors on Malaysian outward foreign direct investment, locational choice and employment - Chen, Jen Eem (2016)
This study investigates the push and the pull factors of outward foreign direct investment (FDI) from Malaysia. The study also examines the effects of outward FDI on employment in Malaysia, particularly skilled and unskilled employment. In examining the push factor, or home country environment, that influences the outward investment, we focus on the role of home government institution. Given that Malaysian outward FDI increased tremendously and at the same time there are some indications that Malaysian firms experience high regulatory costs, we are uncertain if Malaysian outward FDI is driven by the institutional escapism.The results of Autoregressive Distributed Lag (ARDL) confirm that Malaysian outward FDI is driven by GDP, exchange rate, inward FDI, and corporate taxation. This portrays that internationalization strategies of firms are not only relied on home macroeconomic environment but also government institution. The significance of corporate taxation in affecting outward FDI explains that high corporate taxation is a regulatory burden to domestic firms which result in the escape response. In contrast, pull factor refers to the location advantages of host countries that attract foreign investors. Though host countries offer attractive location advantages to the investors, the business risks or uncertainties embedded in the investment cannot be neglected. These uncertainties are translated into transaction costs. The selection of host countries is important as it may bring success or failure to the investing firms. To capture the transaction costs, we employ institutional environment of host countries, common colonization, and geographical distance between home and host countries. The regression estimations reveal that the factors determine Malaysian overseas investments are GDP of host countries, low labour cost, availability of natural resources, quality of governance, geographical distance, and common colonization. Outward investment raises the public fears of job-exporting as a result of firms shifting their production plants abroad. Nevertheless, outward FDI would also stimulate the local employment following the expansion in larger foreign markets. Currently, unemployment is not a serious problem in Malaysia. Nonetheless, the retrenchment of workers in recent years deserves our attention. This leads us to inspect the effects of outward investment on Malaysian employment, specifically skilled and unskilled employment. However, we found no empirical evidence that outward investment is statistically significant in affecting skilled and unskilled employment. Overall, the findings of this thesis give some implications to the investing firms in designing their expansion and penetration strategies such as the mode of investment, amount of investment, source of financing and the other aspects.